Global Insights into the Effectiveness of Moral and Character Education: Implications for 21st Century Learning - Lia Mita Syahri; Adnan Arafani; Inggria Kharisma; Syahrial Syahrial; Tri Handani (Universitas PGRI Yogyakarta, 2026)
Moral-based character education plays a vital role in developing individuals with integrity, responsibility, and empathy, particularly in the context of Society 5.0, where technological advancement must be balanced with strong moral values. This study aims to examine the global effectiveness of moral and character education interventions in enhancing students’ moral understanding and character development. A systematic literature review and meta-analysis were conducted following PRISMA guidelines, synthesizing findings from experimental and quasi-experimental studies published between 2018 and 2025, sourced from major international and national databases. Using a random-effects meta-analytic approach, the results indicate a statistically significant positive effect of moral and character education interventions, despite variations across study contexts. These findings demonstrate that moral and character education contribute meaningfully to the formation of moral identity and ethical awareness. In practice, this study underscores the importance of integrating moral values into curricula and learning practices to strengthen integrity, empathy, and responsibility as essential competencies in 21st-century education. This research provides a comprehensive global synthesis that highlights the original contribution of meta-analytic evidence to the field of moral and character education. Keywords: character education, moral education, values education